ANALISIS KEKUATAN DAN KUALITAS SAMBUNGAN LAS DENGAN VARIASI PENDINGINAN OLI DAN UDARA PADA MATERIAL ASTM A36 DENGAN PENGUJIAN NDT (NON DESTRUCTIVE TEST) - Mohamad Faizal; Syahrul Umam (Bina Teknika, 2018)
Welding is the process of joining two metals to the point of metal recrystallization using either added or not material and using heat energy as a melting agent. In this study, different cooling variations on each specimen were carried out, the material used was ASTM A36 Plate, 3.2 mm diameter E7018 electrode, cooling used with Oil and Air. in the implementation of welding using the SMAW (Shielded Metal Arc Welding) welding method. From the above understanding, research and testing are carried out including tensile tests, radiography / x-rays, and penetrants. The purpose of this study was to determine the strength and quality of welded joints that were not seen with the Destructive Test on the ASTM A36 plate and also to determine the effect of variations in oil and air cooling. From this study it can be found that the tensile strength values for specimen 1 (Oil ) is 373.06 MPa. While the value of tensile strength for specimen 2 (Air) is 365.31 MPa, this means that it has decreased by 7.75 MPa from the tensile strength of specimen 1 (Oil).